Record of an Ectoparasitic Fungus on Eggs of the Neotropical termite Nasutitermes corniger (Blattaria, Isoptera, Termitidae) - Costa-Leonardo, Ana Maria [UNESP]; Janei, Vanelize [UNESP] (Universidade Estadual de Feira de Santana, 2023)
Insects and fungi are abundant in many environments and often interact. However, little information exists on the fungal infestation of insect eggs. Here, we report an entomogenous fungus similar to Hormiscioideus filamentosus (Blackweel & Kimbrough, 1978) infesting eggs of the termite Nasutitermes corniger (Motschulsky, 1855). The fungus arises from egg chorion and has long and simple filaments. The small haustorial cells infiltrate the egg chorion and the fungal thalli number varies from two to ten. Future studies will elucidate the infestation levels of termite eggs by this entomogenous fungus in the Neotropical region and its effects on termite colonies.
Keywords: Ectoparasite; egg parasite; entopathogenic; Nasutitermitinae; social insect